Students' out-of-school science-related experiences and their level of learning interests in science - Sumbilla, Cristie S (Iloilo City University of the Philippines Visayas, 2019)
This qualitative study aimed to develop a repository of fishing community cultural contexts for junior high school mathematics and a contextualized mathematics teaching unit in junior high school following the Community as Learning Laboratory (CoLLab) model. The developed repository was the assimilation of the results of the first three research objectives focused on the identification of the ethnomathematics and cultural contexts for mathematics from two fishing communities while the contextualized mathematics teaching unit was developed through a collaboration with a grade 7 mathematics teacher and a grade 7 class from a fishing community public high school. Results showed that (1) the ethnomathematics of the two fishing communities are manifested in the way the locals practice measuring, quantifying, sorting, classifying, inferring, localizing, designing, and evaluating; (2) the practices of net swing and boat building contain practice-specific problems which can be dialectically ethnomodeled; (3) applications of mathematics topics in junior high school can be demonstrated from the realities of the fishing communities; and (4) the contextualized teaching unit was observed to have facilitated engagement, participation, and cultural awareness from the students. These results were discussed based on the theoretical frameworks of ethnomathematics and dialectical ethnomodeling and in view of the literature. The implications of the results to the knowledge base and practice of culture-based mathematics research and education were discussed and recommendations for future studies were made.
Special Problem (MEd-Biology)--Iloilo City : University of the Philippines Visayas, June 2019.